2021
DOI: 10.3892/mco.2021.2218
|View full text |Cite
|
Sign up to set email alerts
|

The predictive factor for pathological downgrading after prostatectomy in patients with biopsy Gleason score 4+3 or 4+4 prostate cancer

Abstract: The proportion of Gleason pattern (GP) 4 prostate cancers at prostate biopsy has a clinically significant impact on risk stratification for patients with prostate cancer. In pathological diagnosis including GP 4, a biopsy Gleason score (GS) of 3+4 has a more favorable prognosis than a GS of 4+3 and 4+4. However, the discrepancy between biopsy and prostatectomy specimens is well known. The current study investigated the clinical parameters and biopsy specimens associated with pathological downgrading after pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These patients in our study were consequently downgraded from NCCN high-risk PCa to low-intermediate risk. Pathological analysis of the prostatectomy specimens may miss ISUP GG 4 due to the diagnosis of its small lesions ( 31 ). The rate of downgrading may be impacted by inadequate gland sampling on final RP pathological specimens ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…These patients in our study were consequently downgraded from NCCN high-risk PCa to low-intermediate risk. Pathological analysis of the prostatectomy specimens may miss ISUP GG 4 due to the diagnosis of its small lesions ( 31 ). The rate of downgrading may be impacted by inadequate gland sampling on final RP pathological specimens ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…High‐grade lesions on Bx with lower percentage and less positive cores on Bx may be interpreted as primary or secondary pattern, which will be re‐graded to tertiary pattern. Tohi et al 8 looked at patients with a Bx GS 4 + 3 and 4 + 4 undergoing RP, 41.7% of which downgraded to GS ≤ 3 + 4 at RP. The only significant factor predicting downgrading on multivariate logistic analysis was the lower percentage of highest GS cores out of positive Bx cores (odds ratio [OR] = 2.469, p = 0.043).…”
Section: Discussionmentioning
confidence: 99%
“…7 High-grade lesions on Bx with lower percentage and less positive cores on Bx may be interpreted as primary or secondary pattern, which will be re-graded to tertiary pattern. Tohi et al 8 Very few studies have reported the impact of Bx downgrading on the outcomes of patients with PCa, compared with those with no downgrading. Muntener et al 12 reported a cohort of 6625 men and 6.2% encountered downgrading at RP.…”
Section: Discussionmentioning
confidence: 99%